Heterodimeric IL-15 (hetIL-15) reduces circulating tumor cells and metastasis formation improving chemotherapy and surgery in 4T1 mouse model of TNBC - Stravokefalou, Vasiliki; Stellas, Dimitris; Karaliota, Sevasti; Nagy, Bethany A.; Valentin, Antonio; Bergamaschi, Cristina; Dimas, Konstantinos; Pavlakis, George N. (Frontiers in Immunology, 2023)
Immunotherapy has emerged as a viable approach in cancer therapy, with cytokines being of great interest. Interleukin IL-15 (IL-15), a cytokine that supports cytotoxic immune cells, has been successfully tested as an anti-cancer and anti-metastatic agent, but combinations with conventional chemotherapy and surgery protocols have not been extensively studied. We have produced heterodimeric IL-15 (hetIL-15), which has shown anti-tumor efficacy in several murine cancer models and is being evaluated in clinical trials for metastatic cancers. In this study, we examined the therapeutic effects of hetIL-15 in combination with chemotherapy and surgery in the 4T1 mouse model of metastatic triple negative breast cancer (TNBC). hetIL-15 monotherapy exhibited potent anti-metastatic effects by diminishing the number of circulating tumor cells (CTCs) and by controlling tumor cells colonization of the lungs. hetIL-15 treatment in combination with doxorubicin resulted in enhanced anti-metastatic activity and extended animal survival. Systemic immune phenotype analysis showed that the chemoimmunotherapeutic regimen shifted the tumor-induced imbalance of polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) in favor of cytotoxic effector cells, by simultaneously decreasing PMN-MDSCs and increasing the frequency and activation of effector (CD8+T and NK) cells. Tumor resection supported by neoadjuvant and adjuvant administration of hetIL-15, either alone or in combination with doxorubicin, resulted in the cure of approximately half of the treated animals and the development of anti-4T1 tumor immunity. Our findings demonstrate a significant anti-metastatic potential of hetIL-15 in combination with chemotherapy and surgery and suggest exploring the use of this regimen for the treatment of TNBC.